Molecular study of metallo-β-lactamases and integrons in Acinetobacter baumannii isolates from burn patients - Mahnaz Nikibakhsh; Farzaneh Firoozeh; Farzad Badmasti; Kourosh Kabir; Mohammad Zibaei (BMC Infectious Diseases, 2021)
Abstract Background Productions of metallo-β-lactamases enzymes are the most common mechanism of antibiotic resistance to all beta-lactam classes (except monobactams) in Acinetobacter baumannii. MBLs are usually associated with gene cassettes of integrons and spread easily among bacteria. The current study was performed to detect the genes encoding MBLs and integron structures in A. baumannii isolates from burn patients. Methods This study was performed on 106 non-duplicate A. baumannii isolates from burn patients referred to Shahid Motahari Hospital in Tehran. Antibiotic susceptibility of A. baumannii isolates was performed using disk diffusion and broth microdilution method in accordance with the CLSI guidelines. The presence of class 1 integron and associated gene cassettes as well as MBLs-encoding genes including bla VIM, and bla IMP were investigated using PCR and sequencing techniques. Results In this cross-sectional study all (100%) of the A. baumannii isolates examined were multidrug resistant. All isolates were sensitive to colistin and simultaneously all were resistant to imipenem. PCR assays showed the presence of bla VIM and bla IMP genes in 102 (96.2%) and 62 (58.5%) isolates of A. baumannii respectively. In addition, 62 (58.5%) of the A. baumannii isolates carried integron class 1, of which 49 (79.0%) were identified with at least one gene cassette. Three types of integron class 1 gene cassettes were identified including: arr2, cmlA5, qacE1 (2300 bp); arr-2, ereC, aadA1, cmlA7, qacE1 (4800 bp); and aac(3)-Ic, cmlA5 (2250 bp). Conclusion A high prevalence of MBLs genes, especially bla VIM, was identified in the studied MDR A. baumannii isolates. In addition, most of the strains carried class 1 integrons. Furthermore, the gene cassettes arrays of integrons including cmlA5 and cmlA7 were detected, for the first time, in A. baumannii strains in Iran.